Bulaklak ng Maynila - Viva Films (Manila Viva Films, 1999)
The daughter of impoverished parents, Ada's life becomes even more miserable when her father is imprisoned after attempting to rob a bank. For them to survive, Ada and her mother live with Timo, who makes their lives miserable. Ada leaves home and becomes a sexy dancer to survive.
VHS.
Based on the novel "Bulaklak ng Maynila" by Domingo Landicho.
Screenplay, Ricky Lee ; Veronique del Rosario-Corpuz, Vicente G. del Rosario III, producers directed by Joel Lamangan.
Christopher de Leon, Jomari Yllana, Angelu de Leon.
Keywords: Drama; Feature films